Identification and characterization of a core fucosidase from the bacterium Elizabethkingia meningoseptica - Li, Tiansheng (J Biol Chem, 2018)
All reported α-l-fucosidases catalyze the removal of nonreducing terminal l-fucoses from oligosaccharides or their conjugates, while having no capacity to hydrolyze core fucoses in glycoproteins directly. Here, we identified an α-fucosidase from the bacterium Elizabethkingia meningoseptica with catalytic activity against core α-1,3-fucosylated substrates, and we named it core fucosidase I (cFase I). Using site-specific mutational analysis, we found that three acidic residues (Asp-242, Glu-302, and Glu-315) in the predicted active pocket are critical for cFase I activity, with Asp-242 and Glu-315 acting as a pair of classic nucleophile and acid/base residues and Glu-302 acting in an as yet undefined role. These findings suggest a catalytic mechanism for cFase I that is different from known α-fucosidase catalytic models. In summary, cFase I exhibits glycosidase activity that removes core α-1,3-fucoses from substrates, suggesting cFase I as a new tool for glycobiology, especially for studies of proteins with core fucosylation.